Effectiveness of Intermittent Preventive Treatment in Pregnancy with Sulphadoxine-Pyrimethamine against Submicroscopic falciparum Malaria in Central Region, Ghana - Nwaefuna, Ekene K. (J Parasitol Res, 2015)
Malaria infections undetectable by microscopy but detectable by Polymerase Chain Reaction (PCR) (submicroscopic malaria) are common in endemic areas like Ghana. Submicroscopic malaria has been linked with severe pregnancy outcomes as well as contributing to malaria transmission. In this cross-sectional study 872 consenting pregnant women (gestation ≥ 20 weeks) were recruited from 8 hospitals in Central Region, Ghana, between July and December 2009. Malaria infection was detected by microscopy and PCR. Haemoglobin was measured and anaemia was defined as haemoglobin lower than 11 g/dL. Majority of the women, 555 (63.6%), were Intermittent Preventive Treatment in Pregnancy with Sulphadoxine-Pyrimethamine (IPTp-SP) users while 234 (36.4%) were nonusers. The prevalence of malaria by microscopy was 20.9% (182/872) and 9.7% (67/688) of microscopy negative women had submicroscopic malaria. IPTp-SP usage significantly (odds ratio = 0.13, 95% confidence interval = 0.07–0.23, p = 0.005) reduced the prevalence of submicroscopic malaria as more nonusers (51/234) than users (16/454) were PCR positive. After controlling for other variables the effect of IPTp-SP remained statistically significant (odds ratio = 0.11, 95% confidence interval = 0.02–0.22, p = 0.006). These results suggest that Intermittent Preventive Treatment with Sulphadoxine-Pyrimethamine is useful in the reduction of submicroscopic malaria in pregnancy.